Dyslexia Risk Screening System based Fuzzy Logic - Jumadi, Nur Anida; Mun, Ng Li; Morsin, Marlia; Mohtaram, Saifuddin (International Journal of Engineering and Technology, 2018)
It is estimated that more than 314, 000 of Malaysian young children are dyslexic, which means having difficulty particularly in reading and spelling. Manual dyslexia screening test ages 6 to 10 years old (in Bahasa Malaysia) produced by Persatuan Dyslexia Malaysia contains 10 sets of tests including reading, rapid naming and pseudowords. However, confirmation of dyslexic status takes several days as the test scores are manually calculated. Therefore, a rapid computerized dyslexia risk screening tool based fuzzy logic has been proposed here. Using the scores obtain from four main tests namely as rapid naming, one-minute reading, two-minute spelling and pseudowords, the fuzzy system is able to determine dyslexic condition instantly. The main fuzzy inputs using pre-existed scores of 17 dyslexia subjects (3 girls and 14 boys) resulted promising system’s accuracy (94.1 %) when classifying dyslexic risk in young children. In the future, this research will include non-dyslexia as well as other learning disability subjects for accuracy clarification towards non-dyslexia classification.